Cognitive impairment no dementia and associations with health literacy, self-management skills, and functional health status. Issue 9 (September 2020) - Lovett, Rebecca M.; Curtis, Laura M.; Persell, Stephen D.; Griffith, James W.; Cobia, Derin; Federman, Alex; Wolf, Michael S.
Highlights: CIND may be more prevalent than expected in diverse, primary care settings. CIND is associated with reduced ability to independently self-manage health. Self-care difficulty may be an indirect means of detecting early cognitive changes. Targeting self-care may be a practical approach to manage health in CIND adults. Abstract: Objectives: To determine the prevalence of cognitive impairment no dementia (CIND) among a diverse, community-based population, and establish associations between CIND and health literacy, chronic disease self-management and functional health status. Methods: 863 primary care adults without dementia aged 55–74. Adjusted logistic and linear regressions were used to assess associations between CIND (None, Mild, Moderate/Severe) and outcomes. Results: 36 % participants exhibited CIND. It was strongly associated with limited health literacy (Newest Vital Signs: Mild [OR 3.25; 95 % CI 1.93, 5.49], Moderate/Severe [OR 6.45; 95 % CI 3.16, 13.2]; Test of Functional Health Literacy in Adults: Mild [OR 3.46; 95 % CI 2.08, 5.75], Moderate/Severe [OR 8.82; 95 % CI 4.87, 16.0]; all p's < 0.001) and poor chronic disease self-management (Mild [B = −11.2; 95 % CI −13.5, -8.90], Moderate/Severe CI [B = −21.0; 95 % CI −23.6, −18.4]; both p's < 0.001). Associations between CIND and functional health status were non-significant. Conclusions: CIND was prevalent in this cohort, and strongly associated with requisite skills for managing everyday health needs. Practice Implications: Attention to subtle declines in chronic disease self-care may assist with CIND identification and care management within this population. When CIND is observed, clinicians should also expect and address difficulties with self-management.